Unifying Electronic Dictionaries of Swahili into the DICT Format - Wójtowicz, Beata (Investigationes Linguisticae, 2004)
Electronic Swahili dictionaries differ in their form, format and content. Due to legal aspects, it may be impossible to consolidate them into a single one, however it is feasible to access them in a uniform way. In the present paper, the use of TEI and DICT format for this purpose is discussed.